Effects of coffee intake on skeletal muscle microvascular reactivity at rest and oxygen extraction during exercise: a randomized cross-over trial - Bin Leng; Haizhen Huang; Chuan Zhang (Taylor & Francis Group, 2024)
Purpose The effects of coffee ingestion on skeletal muscle microvascular function are not well understood. This study aimed to investigate the acute effects of coffee intake with varying levels of caffeine on skeletal muscle microvascular reactivity at rest and oxygen extraction during maximal incremental exercise in physically active individuals.Methods Twenty healthy young male participants were administered coffee with low caffeine (3 mg/kg body weight; LC), high caffeine (6 mg/kg body weight; HC), and placebo (decaf) in different sessions. Skeletal muscle reactivity indexes, including tissue saturation index 10s slope (TSI10) and TSI half time recovery (TSI ½) following 5-minute ischemia were measured at rest and were measured at baseline and post-coffee consumption using near-infrared spectroscopy (NIRS). Post-coffee intake, NIRS was also used to measure microvascular oxygen extraction during exercise via maximal incremental exercise. Peak oxygen consumption and peak power output (Wpeak) were simultaneously evaluated.Results Post-coffee consumption, TSI10 was significantly higher in the LC condition compared to placebo (p = 0.001) and significantly higher in the HC condition compared to placebo (p < 0.001). However, no difference was detected between LC and HC conditions (p = 0.527). HC condition also showed significant less TSI ½ compared to placebo (p = 0.005). However, no difference was detected for microvascular oxygen extraction during exercise, despite the greater Wpeak found for HC condition (p < 0.001) compared to placebo.Conclusion Coffee ingestion with high caffeine level (6 mg/kg body weight) significantly enhanced skeletal muscle reactivity at rest. However, the improvement of exercise performance with coffee intake is not accompanied by alterations in muscle oxygen extraction.